RETRACTED: Development of an information system to improve the efficiency of custom production - Orlov Vasiliy; Tynchenko Vadim; Kukartseva Svetlana (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001